Manfaat Pembelajaran Renang untuk Pertumbuhan dan Perkembangan Anak di Sekolah Dasar - Mulyana, Agus; Pingkan, Anggista Dwiana; Yulianti, Delis; Luthfiatunnisa, Farah Fauziah; Shidiqqa, Queeny Qolbi Ash; Sabirah, Ruzaina; Azzahra, Siti Fatimah (Indo-MathEdu Intellectuals Journal, 2024)
Swimming increases muscle mass, loses weight, improves heart and lung health, controls stress, overcomes nerve compression, relieves joint pain, addresses insomnia, and improves sleep quality. In addition, swimming is also very suitable for people with asthma, helping to increase lung capacity and train respiratory control. This article aims to find out the benefits of learning to swim for the growth and development of children in elementary school. This research uses a qualitative approach through literature study. The main source of data for this research is scientific articles published on the database on google scholar which can be accessed online with the keywords used in searching for journals are "Swimming, Sports, Elementary School, Benefits, Swimming Techniques". Data analysis is carried out qualitatively, namely data reduction, data presentation, and conclusion drawing. Data analysis was carried out qualitatively, namely data reduction, data presentation, and conclusion drawn. The results of the analysis show that swimming learning in elementary school has an important role in supporting children's growth and development. This sport of swimming has many benefits and advantages to help children's growth and development, relationships between children and others, increase confidence, and can also be used as a fun activity because of the cold stimulus that can refresh the body. Therefore, swimming helps children develop important life skills and improve their quality of life